A Comprehensive Analysis of Calmodulin-Like Proteins of Glycine max Indicates Their Role in Calcium Signaling and Plant Defense Against Insect Attack - Yadav, Manisha; Pandey, Jyotsna; Chakraborty, Amrita; Hassan, Md. Imtaiyaz; Kundu, Jiban Kumar; Roy, Amit; Singh, Indrakant Kumar; Singh, Archana (Frontiers in Plant Science, 2022)
The calcium (Ca2+) signaling is a crucial event during plant-herbivore interaction, which involves a transient change in cytosolic Ca2+ concentration, which is sensed by Ca2+-sensors, and the received message is transduced to downstream target proteins leading to appropriate defense response. Calmodulin-like proteins (CMLs) are calcium-sensing plant-specific proteins. Although CMLs have been identified in a few plants, they remained uncharacterized in leguminous crop plants. Therefore, a wide-range analysis of CMLs of soybean was performed, which identified 41 true CMLs with greater than 50% similarity with Arabidopsis CMLs. The phylogenetic study revealed their evolutionary relatedness with known CMLs. Further, the identification of conserved motifs, gene structure analysis, and identification of cis-acting elements strongly supported their identity as members of this family and their involvement in stress responses. Only a few Glycine max CMLs (GmCMLs) exhibited differential expression in different tissue types, and rest of them had minimal expression. Additionally, differential expression patterns of GmCMLs were observed during Spodoptera litura-feeding, wounding, and signaling compound treatments, indicating their role in plant defense. The three-dimensional structure prediction, identification of interactive domains, and docking with Ca2+ ions of S. litura-inducible GmCMLs, indicated their identity as calcium sensors. This study on the characterization of GmCMLs provided insights into their roles in calcium signaling and plant defense during herbivory.